مقارنة بعض طرائق الانحدار الخطي المتعدد بالاعتماد على القيم والمتجهات الذاتية لمصفوفة الارتباط - الدكتور موفق محمد توفيق القصاب; صالح مؤيد شكر (PROSPECTIVE RESEARCHES, 2023)
In this research, we present the estimates of the parameters for the least square, Eigen and ridge regression methods depending on the eigen values and vectors of the correlation matrix of both dependent and independent variables. A general mathematical formula relating these estimators in have been investigated in this research.